2006
DOI: 10.1111/j.1742-4658.2006.05310.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive activities of DNA polymerases during human DNA replication

Abstract: DNA polymerases (pols) have a central role in DNA replication and maintenance of chromosomal DNA [1]. At least 14 pols have been identified in the mammalian cell, but only three -pols a, d and e -are needed to synthesize the bulk of DNA during nuclear DNA replication. These pols are structurally related, belonging to the family B DNA polymerases [2]. Nonetheless, all three perform additional roles in other DNA transactions as well as transduce signals of cell cycle control and DNA damage response [1].Only pol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 73 publications
(114 reference statements)
2
15
0
Order By: Relevance
“…Studies in yeast show that Pols and ␦ synthesize and proofread opposite DNA strands at defined replication origins (10,(14)(15)(16)(17)(18). However, Pols and ␦ also may act independently (33,34), and some replication forks may involve only 1 proofreading polymerase (14). Considered together, our results suggest a model in which Pol and Pol ␦ replicate and proofread different regions of the mouse genome encoding tissue-specific genes that suppress cancer or are required for embryogenesis.…”
Section: Resultsmentioning
confidence: 73%
“…Studies in yeast show that Pols and ␦ synthesize and proofread opposite DNA strands at defined replication origins (10,(14)(15)(16)(17)(18). However, Pols and ␦ also may act independently (33,34), and some replication forks may involve only 1 proofreading polymerase (14). Considered together, our results suggest a model in which Pol and Pol ␦ replicate and proofread different regions of the mouse genome encoding tissue-specific genes that suppress cancer or are required for embryogenesis.…”
Section: Resultsmentioning
confidence: 73%
“…86 In human cells, studies of the localization of Pol δ and Pol ε as well as analysis of their association with chromatin and lamins have suggested that they may act partly independently during S phase progression. [87][88][89] While Pol δ3 might be excluded as a player in leading-strand synthesis, the idea that Pol δ4 could participate in leading-strand synthesis is still an open possibility. Whether and why both Pol δ3 and Pol δ4 participate in lagging-strand synthesis remain questions to be answered.…”
Section: 70mentioning
confidence: 99%
“…A study using different experimental approaches to examine the association of Pol d, Pol e, and Pol a at different stages of the S phase in HeLa cells has provided evidence that both Pol e and Pol d participate in chromosomal DNA replication and that Pol e plays a Environmental and Molecular Mutagenesis. DOI 10.1002/em greater role in early S phase while Pol d plays a greater role in late S phase [Rytkonen et al, 2006].…”
Section: Role Of Pol D At the Replication Forkmentioning
confidence: 99%